Basal Cell Adenoma of the Parotid Gland: A Case Report and Review of the Literature - Chen, BS, Julia; Feng, MD, PhD*, Dian (North American Journal of Medicine and Science, 2023)
Basal cell adenoma (BCA) is a rare benign biphasic epithelial neoplasm of salivary gland composed of basaloid cells and inner ductal epithelial cells. Here, we present a case of a 25-year-old man with a long-standing history of swelling of the left side of the cheek. The specimen was sent for intraoperative frozen section consultation. The tumor appeared to be solid and cystic with a thin capsule and was composed of a biphasic basaloid cells forming tubular and trabecular glands, and fibromyxoid stroma. The differential diagnosis in this case encompasses a broad spectrum of biphasic salivary gland epithelial neoplasms, including benign basal cell adenoma, pleomorphic adenoma, and malignant adenoid cystic carcinoma and basal cell adenocarcinoma. To enhance our proficiency in intraoperative consultation and final diagnosis of biphasic basaloid neoplasms of the salivary gland, we present this rare case along with a comprehensive review of the literature. [N A J Med Sci. 2023;16(1):001-005. DOI: 10.7156/najms.2023.1601001] Key Words: Basal cell adenoma, Parotid gland, Differential diagnosis